Incomplete intestinal absorption of fructose. Issue 8 (August 1984) - Kneepkens, C M; Vonk, R J; Fernandes, J
Abstract : Intestinal D-fructose absorption in 31 children was investigated using measurements of breath hydrogen. Twenty five children had no abdominal symptoms and six had functional bowel disorders. After ingestion of fructose (2 g/kg bodyweight), 22 children (71%) showed a breath hydrogen increase of more than 10 ppm over basal values, indicating incomplete absorption: the increase averaged 53 ppm, range 12 to 250 ppm. Four of these children experienced abdominal symptoms. Three of the six children with bowel disorders showed incomplete absorption. Seven children were tested again with an equal amount of glucose, and in three of them also of galactose, added to the fructose. The mean maximum breath hydrogen increases were 5 and 10 ppm, respectively, compared with 103 ppm after fructose alone. In one boy several tests were performed with various sugars; fructose was the only sugar incompletely absorbed, and the effect of glucose on fructose absorption was shown to be dependent on the amount added. It is concluded that children have a limited absorptive capacity for fructose. We speculate that the enhancing effect of glucose and galactose on fructose absorption may be due to activation of the fructose carrier. Apple juice in particular contains fructose in excess of glucose and could lead to abdominal symptoms in susceptible children.